The Impact of Mobile-Assisted Hybrid Dynamic Assessment on Arabic Language Leaners’ Reading Comprehension Performance - Mustiah, Mustiah; Dayat, Dayat; Sadek, Nihal (Universitas Pendidikan Mandalika, 2024)
Dynamic assessment is unity of assessment and instruction based on the sociocultural theory in which mediation is gradually provided to promote the cognitive development. This study mainly aimed to explore the quantitative and qualitative impact of mobile-assisted hybrid dynamic assessment (MAHDA) on Islamic religious Education (IRE) learners’ Arabic reading comprehension (ARC). This recent study employed a sequential explanatory mixed-methods design and involved twenty participants assigned into experimental and control groups. All groups received pre-and post-tests to compare the intervention. The experimental group was mediated through the MAHDA procedure for two months and the control group received conventional instruction. The interview with the participants was also conducted to assess the learners’ perception of the mediation strategies of MAHDA. The pre- and post-test were analyzed by t-test and the transcribed interviews were thematically analyzed. Quantitatively, the results showed a meaningful distinction between the two groups. It highlighted that MAHDA was significantly effective to enhance the learners’ knowledge of ARC. The qualitative findings also indicated that the participants felt satisfied with the MAHDA in improving the learners’ ARC abilities and social interaction. One of the implications of this research is to promote the use of mobile learning as mediation DA framework to teach various features of Arabic including reading comprehension of Arabic. Further research is required MAHDA with a larger site and samples to generate the effectiveness of MAHDA.